2015
DOI: 10.1371/journal.pone.0127589
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Radio-Density Is an Independent Predictor of Response and Outcomes in Follicular Lymphoma Treated with Chemoimmunotherapy

Abstract: Skeletal muscle radio-density (SMD) measures muscle radiation attenuation (in Hounsfield Units, HU) on computed tomography (CT) scans. Low SMD is prognostic of poor survival in melanoma, however its significance is unknown for hematologic malignancies. We performed a single institution, retrospective review of all follicular lymphoma (FL) patients who received chemoimmunotherapy from 2004–2009. Patient demographics, FL International Prognostic Index 1 (FLIPI-1), progression free (PFS) and overall survival (OS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
61
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 26 publications
8
61
1
Order By: Relevance
“…To our knowledge, no studies have been reported that use similar methodology to investigate muscle radiation attenuation in patients with pancreatic cancer. When looking at studies in other malignancies with similar methodology as the present study, low muscle radiation attenuation has consistently been associated with poor survival in hepatocellular carcinoma, respiratory and colorectal cancer, and follicular lymphoma . Skeletal muscle area was not associated with outcomes in the present study, which agrees with previous findings in pancreatic cancer patients .…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, no studies have been reported that use similar methodology to investigate muscle radiation attenuation in patients with pancreatic cancer. When looking at studies in other malignancies with similar methodology as the present study, low muscle radiation attenuation has consistently been associated with poor survival in hepatocellular carcinoma, respiratory and colorectal cancer, and follicular lymphoma . Skeletal muscle area was not associated with outcomes in the present study, which agrees with previous findings in pancreatic cancer patients .…”
Section: Discussionsupporting
confidence: 90%
“…In this study, low SMD appeared to be more prognostic of poor patient survival than skeletal muscle index. Low SMD is also similarly more prognostic than skeletal muscle index in melanoma, renal cell cancer, and follicular lymphoma . It is important to note that cut‐point analysis in our study independently established the same SMD parameters defined in solid organ malignancies—providing early validation of its continued use of these cut points in DLBCL .…”
Section: Discussionsupporting
confidence: 57%
“…Clinically, sarcopenia and cachexia are related in cancer patients, both of which have been shown to be poor prognostic indicators . Low SMD, though, appears to be more prognostic than sarcopenia in both solid and haematologic cancers . It was previously observed that SMD was prognostic of survival in follicular lymphoma, an indolent form of non‐Hodgkin lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…In other tumours, such as follicular lymphoma, melanoma, and metastatic renal cell and gastric carcinoma, no association between skeletal muscle mass and survival was shown, whereas skeletal muscle density was an independent prognostic factor [28, 30-33]. The similarity between these studies and the current study is the aggressive course of the disease, which may have led to the inability to accurately predict outcome.…”
Section: Discussionmentioning
confidence: 44%